Apocryphal Joyce: fuga per canonem - Holtkamp, G (2018)
This dissertation explores the idea of an 'apocryphal Joyce' by tracing the evolving apocryphal conflicts — crises of truth, doubt, authority and authorship — in his work. Building on the original meaning of 'apocryphal' as hidden writing (apocrypha scripta), this dissertation follows what it calls Joyce’s fuga per canonem: his flight through the canon. This phrase, from his notes for Ulysses, is especially apt for Joyce given his early connection of the writer as craftsman and apostate with Daedalus, the mythic figure whose wings symbolized for Joyce the liberated intellect of the artist. With the frame of the canon and the canonical versus 'hidden writing' and the apocryphal this dissertation traces Joyce's various styles of interrogating canonical, authoritative discourse through transgressive or illicit forms of writing. Specifically, this dissertation shows how these various 'apocryphal modes' of Joyce converge as a growing movement of flight. This 'taking flight' shows Joyce’s evolution from his depictions of spiritual and psychological unrest in his early work into his creation of a poetics of unrest, his prodigious invasion and evasion of canonical categories in the transgressive somatic imagery of Ulysses. Finally, this dissertation offers new insights into the humor of Finnegans Wake by exploring the heretofore overlooked comedy of Joyce's many references to canonical and apocryphal scripture in his depiction of the authors of the four canonical Gospels, 'Mamalujo,' and the controversy of the apocrypha scripta they seek, the spurious 'hen's letter.' Ultimately we see that the apogee of Joyce's flight is his embrace of the artist's intellectual liberation, creativity and insight in the apocryphal positions of the outlaw, the marginalized, the exiled and the disenfranchised. The radical experiences and alternative systems of value of these vantages become, as we will see, Joyce's most fundamental creative mode.